1016. Long-term Follow-up after Fecal Microbiota Transplantation via Colonoscopy or Freeze-Dried Capsules for Recurrent Clostridioides difficile infection. (4th December 2021) - Donskey, Curtis; Hecker, Michelle; Rosero, Christian
Abstract: Background: Background: Fecal microbiota transplantation (FMT) is effective for treatment of recurrent Clostridioides difficile infection (CDI). However, limited data are available on the durability of FMT, especially after FMT via capsules and with more than 1 year of follow-up. Figure. Outcomes after FMT in 162 patients with recurrent CDI Methods: Methods: A retrospective cohort study was conducted for all patients undergoing FMT from April 2013–November 2020 in a tertiary care hospital. Initial management was considered successful if 1 to 3 FMTs resulted in improved symptoms with no diagnosis of recurrent CDI at 3 months after the initial FMT. Medical record review and telephone interviews were conducted to determine the frequency of recurrent CDI after initial successful management. Results: Results: One-hundred sixty-two patients received 228 FMT procedures (range, 1 to 5), including 78 (34%) via colonoscopy, 144 (63%) via freeze-dried oral capsules, and 6 (3%) via nasogastric/duodenal/PEG tube. The median follow-up time after initial FMT was 61 months (range, 10 to 99 months). Initial management was successful in 132 (81%) patients after 1 FMT and in 24 (14%) patients with 1-2 additional FMTs (Figure). During long-term follow-up, 29 recurrences occurred in 22 of 159 (14%) patients evaluated. Ten (34%) of the recurrences occurred greater than 12 months after the initial FMT. Of the 22 patients with recurrence after 3 months, 16 (73%) were successfully managed with CDI therapy or additional FMT. Conclusion: Conclusion: In our center, FMT via colonoscopy or freeze-dried capsules was very successful in initial management of recurrent CDI and 85% had a durable response with no further recurrences. However, more than 1 FMT procedure was often required to achieve initial success and to manage late recurrences. Disclosures: All Authors : No reported disclosures